Pengaruh Gaya Kepemimpinan Dan Stres Kerja Terhadap Kinerja Karyawan Perbankan Dengan Dimoderasi Oleh Motivasi - Senda Yunita Leatemia (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to examine the effect of leadership style and work stress on the performance of banking employees moderated by motivation. This study is primary data obtained from distributing questionnaires directly to employees of Bank Maluku, Bank Mandiri, BNI, BTN, and BRI. Data processing was carried out using multiple linear regression analysis and MRA. The results in this study show that leadership style has a positive effect on employee performance, work stress has a negative effect on employee performance, based on the moderating test of work motivation moderates leadership style on employee performance, and work motivation moderates work stress on employee performance.